2015
DOI: 10.1016/j.rboe.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal artery injury during posterior cruciate ligament reconstruction

Abstract: This study reports a case of popliteal artery injury during arthroscopic reconstruction of the posterior cruciate ligament. The evolution of the injury is described and comments are made regarding the anatomy of this artery and potential risks of this surgical technique. This study had the aims of alerting the medical community, especially knee surgeons, regarding a severe surgical complication and discussing the ways of preventing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Neurovascular injury, although rare, is the most feared complication of PCL reconstruction. Despite the proximity of the neurovascular structures to the PCL, only one case study was found describing a popliteal artery injury during a PCL reconstruction 56. Among the long-term studies evaluating operative management of PCL reconstructions, only three reported on complications of the procedures 25,30,44.…”
Section: Resultsmentioning
confidence: 99%
“…Neurovascular injury, although rare, is the most feared complication of PCL reconstruction. Despite the proximity of the neurovascular structures to the PCL, only one case study was found describing a popliteal artery injury during a PCL reconstruction 56. Among the long-term studies evaluating operative management of PCL reconstructions, only three reported on complications of the procedures 25,30,44.…”
Section: Resultsmentioning
confidence: 99%
“…Vascular injury to the popliteal artery is a potential complication during screw fixation of tibial tubercle fractures 4–7. Thus, knowledge of the anatomical variation of the popliteal artery in pediatric patients may provide important insight during tibial tubercle fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular injury to the popliteal artery is a potential complication during screw fixation of tibial tubercle fractures. [4][5][6][7] Thus, knowledge of the anatomical variation of the popliteal artery in pediatric patients may provide important insight during tibial tubercle fracture fixation. We found sagittal measurements to be similar at the proximal 3 levels, averaging 5 cm, and tapering distally, decreasing to a mean width of 4 cm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations